The Determinants of Inclusive Economic Growth in Yogyakarta - Ibnu Hidayat; Sri Mulatsih; Wiwiek Rindayati (Jurnal Economia, 2020)
Abstract: Inclusive economic growth is related to how economic growth achieved can reduce poverty, income inequality, and unemployment. The purpose of this study is to analyze factors that influence inclusive economic growth in Yogyakarta. This study used panel data from 2011 to 2017. Estimation of the model (simultaneous equations) used the Two-Stage Least Square (2SLS) method. The result of the analysis showed that Factors that have a positive impact on inclusive economic growth are household consumption, exports of service/goods, foreign investment, domestic investment, per capita income, and average length of year of study. Whereas the negative influence is the level of open unemployment and imports of service/goods. An increase in household consumption by 2% willincrease gross regional domestic product by 1.5%, decrease the open unemployment rate by 3.0%, decrease poverty by 10.7%, and decrease income inequality by 5.5%.Keywords: inclusive economic growth. simultaneous equations. 2SLS Faktor-Faktor yang Mempengaruhi Pertumbuhan Ekonomi Inklusif di YogyakartaAbstrak: Pertumbuhan ekonomi dikatakan inklusif jika memberi manfaat bagi masyarakat bawah seperti dapat mengurangi kemiskinan, ketimpangan pendapatan, dan pengangguran. Tujuan dari penelitian ini adalah untuk menganalisis faktor-faktor yang mempengaruhi pertumbuhan ekonomi inklusif di Daerah Istimewa Yogyakarta. Penelitian ini menggunakan data panel dari tahun 2011 hingga tahun 2017. Estimasi model (persamaan simultan) menggunakan metode Two Stage Least Square (2SLS). Analisis menunjukkan bahwa faktor-faktor yang memiliki pengaruh positif terhadap pertumbuhan ekonomi inklusif adalah konsumsi rumah tangga, ekspor barang/jasa, investasi asing, investasi domestik, pendapatan perkapita, dan rata-rata lama sekolah. Sedangkan pengaruh negatifnya adalah tingkat pengangguran terbuka dan impor barang/jasa. Peningkatan konsumsi rumah tangga sebesar 2% akan meningkatkan produk domestik regional bruto sebesar 1.5%, menurunkan tingkat pengangguran terbuka sebesar 3.0%, menurunkan kemiskinan sebesar 10.7% dan menurunkan ketimpangan pendapatan sebesar 5.5%.Kata kunci: pertumbuhan ekonomi inklusif. persamaan simultan. 2SLS